Immunoinformatics Design and Assessment of a Multiepitope Antigen (OvMCBL02) for Onchocerciasis Diagnosis and Monitoring - Bernis Neneyoh Yengo; Cabirou Mounchili Shintouo; An Hotterbeekx; Ntang Emmaculate Yaah; Robert Adamu Shey; Jusal Quanico; Geert Baggerman; Lawrence Ayong; Luc Vanhamme; Rose Njemini; Jacob Souopgui; Robert Colebunders; et al. (Diagnostics, 2022)
Onchocerciasis is a Neglected Tropical Disease that has a significant socioeconomic impact, especially in Sub-Saharan Africa. Numerous reports indicate that the Expanded Special Project for the Elimination of Neglected Tropical Diseases needs novel diagnostic tools before achieving its goal of successful elimination of onchocerciasis in Africa. The current diagnostic tests are either invasive, insensitive, or not applicable in the field and about 25% of persons infected cannot mount immune responses against the single antigen used in the only approved Ov-16 serological test. In the quest to identify novel biomarkers that can be used to certify that a patient is free from the disease, evaluate the progress of elimination programmes, and conduct post elimination surveillances, mass spectrometric analysis of Onchocerca volvulus crude extract revealed that 1392 proteins are expressed in the adult and microfilariae stages of the parasite. Computational analysis predicted six of the proteins as O. volvulus potential diagnostic targets. Linear B-epitopes were predicted from the six proteins and used to construct a multiepitope antigen (OvMCBL02). Serological analysis revealed that the OvMCBL02 test significantly differentiated between serum samples of onchocerciasis patients from the Kombone Health Area in the South West Region of Cameroon (n = 63) and control serum samples from Rwanda (n = 29) and Europe (n = 26) as well as between serum samples from the onchocerciasis hyperendemic region of Kombone Health Area (n = 63) and the hypoendemic region of Bandjoun Health District (n = 54). Interestingly, the test did not cross-react with serum samples from patients suffering from related nematode infections, thereby suggesting that further characterization of the OvMCBL02 multiepitope antigen will render it an additional member of the diagnostic toolbox for the elimination of onchocerciasis.